Post-LASIK dry eye disease: A comprehensive review of management and current treatment options - Tamimi, Atena; Sheikhzadeh, Farzad; Ezabadi, Sajjad Ghane; Islampanah, Muhammad; Parhiz, Peyman; Fathabadi, Amirhossein; Poudineh, Mohadeseh; Khanjani, Zahra; Pourmontaseri, Hossein; Orandi, Shirin; Mehrabani, Reyhaneh; Rahmanian, Mohammad; et al. (Frontiers in Medicine, 2023)
Laser-Assisted In Situ Keratomileusis (LASIK) is a unique corneal stromal ablation method to laser ablation with excimer laser beneath a corneal dome-shaped, while surface ablation methods, such as photorefractive keratectomy, include removing epithelium and cutting of the Bowman’s layer and the stromal tissue of anterior corneal. Dry eye disease (DED) is the most common complication occurring after LASIK. DED is a typical multi-factor disorder of the tears and ocular surface that occurs when the eyes fail to produce efficient or adequate volumes of tears to moisturize the eyes. DED influences life quality and visual perception, as symptoms often interfere with daily activities, such as reading, writing, or using video display monitors. Generally, DED brings about discomfort, symptoms of visual disturbance, focal or global tear film instability with possible harm to the ocular surface, the increased osmolarity of the tear film, and subacute inflammation of the ocular surface. Almost all patients develop a degree of dryness in the post-operative period. Detection of pre-operative DED and committed examination and treatment in the pre-operative period and continuing treatments post operatively leads to quicker healing, fewer complications and improved visual outcome. To improve patient comfort and surgical outcomes early treatment is required. Therefore, in this study, we aim to comprehensively review studies on management, and current treatment options for post-LASIK DED.